Schmallenberg virus epidemiology and regional control strategies: diagnostics, vaccines, and vector management - Wang, Jing; Jia, Qi; Xiang, Haoyu; Wang, Fang; Sun, Chao; Chang, Jitao; Jiang, Zhigang; Yin, Xin (Frontiers in Cellular and Infection Microbiology, 2025)
Schmallenberg virus (SBV) is an emerging orthobunyavirus transmitted by Culicoides midges. It poses a serious global health threat to ruminants, especially during pregnancy, causing abortion, stillbirths, and congenital malformations. Since its first outbreak in 2011, SBV has spread across Europe and other regions. Its transmission has expanded due to global climate change and increased animal trade, resulting in recurrent outbreaks in endemic regions and a growing risk of introduction into non-endemic areas. This situation highlights the urgent need for improved control strategies. This review summarizes the pathogenic and epidemiological characteristics of SBV and provides an overview of recent advancements in diagnostic approaches, vaccine development, and vector control. Diagnostic approaches, such as serological assays and nucleic acid-based tests, have become the primary tools for SBV detection. However, their applicability in clinical settings still requires further optimization. In terms of vaccine development, existing inactivated vaccines have limitations, including the inability to distinguish between vaccinated and infected animals. This has driven the development of next-generation vaccines, such as recombinant protein, viral vector, and mRNA-based platforms. For vector control, integrated approaches combining chemical, ecological, and biological strategies have been proposed to interrupt the transmission of the virus by Culicoides midges. Additionally, this review emphasizes the necessity of region-specific control strategies tailored to the differing epidemiological contexts. In endemic regions, comprehensive measures, including pathogen surveillance, vaccination programs, and Culicoides control, are critical. In non-endemic regions, the focus should be on enhancing border biosecurity, monitoring international trade, and establishing early warning systems. These strategies not only provide a scientific foundation for SBV control but also offer practical guidance for managing the spread of similar vector-borne viruses globally.